1,8-diazabicyclo(6.6.6)eicosane, 1,8-diazabicyclo(6.6.5)nonadecane and 1,8-diazabicyclo(6.6.4)octadecane and their diprotonated forms - Pool, Brett; Balalaie, Saeed; Kunze, Andreas; Schilling, Gerhard; Bischof, Peter; Gleiter, Rolf (European journal of organic chemistry, 2004)
The preparation of the title compounds 9−11 was achieved by catalytic hydrogenation of 1,8-diazabicyclo[6.6.6]eicosa-4,11-diyne (13), 1,8-diazabicyclo[6.6.5]nonadeca-4,11-diyne (14), and 1,8-diazabicyclo[6.6.4]octadeca-4,11-diyne (15), respectively. As catalyst we used Pd(OH)2 on carbon. NMR studies on 9−11 revealed an in/in conformation at the bridgehead positions. Treatment of 9−11 with an excess of trifluoroacetic acid yielded, in a kinetically controlled reaction, mixtures of the out/out and in/out diprotonated species [9·2H]2+, [10·2H]2+ and [11·2H]2+. The thermodynamically controlled species, the corresponding in/in conformers, are formed at higher temperatures and longer reaction times. The experimental observations are supported by AM1 calculations. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)
Im Titel steht 6.6.6, 6.6.5 und 6.6.4 jeweils in eckiger Klammer
Dedicated to Professor Zvonimir B. Maksić on the occasion of his 65th birthday
Gesehen am 27.10.2020
Keywords: Festschrift